Activity of Metabotropic Glutamate Receptor 4 Suppresses Proliferation and Promotes Apoptosis With Inhibition of Gli-1 in Human Glioblastoma Cells - Zhang, Zhichao; Zheng, Xiaoyan; Luan, Yan; Liu, Yingfei; Li, Xingxing; Liu, Chongxiao; Lu, Haixia; Chen, Xinlin; Liu, Yong (Frontiers in Neuroscience, 2018)
Glioblastoma multiforme (GBM) is the most lethal glioma variant in the adult brain and among the deadliest of human cancers. Increasing evidence has shown that metabotropic glutamate receptor subtype 4 (mGluR4) expression may play roles in regulating the growth of neural stem cells as well as several cancer cell lines. Here, we investigated the effects of mGluR4 on the growth and apoptosis of the LN229 GBM cell line. Involvement of Gli-1, one of the key transcription factors in the sonic Hedgehog (SHH) signaling pathway, was further explored. In this study, mGluR4 was activated using selective agonist VU0155041; and gene-targeted siRNAs were used to generate loss of function of mGluR4 and Gli-1 in LN229 cells. The results demonstrated that LN229 cells expressed mGluR4 and the agonist VU0155041 decreased cell viability in a dose- and time-dependent manner. Activation of mGluR4 inhibited cyclin D1 expression, activated pro-caspase-8/9/3, and disrupted the balance of Bcl-2/Bax expression, which indicated cell cycle arrest and apoptosis of LN229 cells, respectively. Furthermore, Gli-1 expression was reduced by mGluR4 activation in LN229 cells, and downregulation of Gli-1 expression by gene-targeted siRNA resulted in both inhibition of cell proliferation and promotion of apoptosis. Moreover, VU0155041 treatment substantially blocked SHH-induced cyclin D1 expression and cell proliferation, while increasing TUNEL-positive cells and the activation of apoptosis-related proteins. We concluded that activation of mGluR4 expressed in LN229 cells could inhibit GBM cell growth by decreasing cell proliferation and promoting apoptosis. Further suppression of intracellular Gli-1 expression might be involved in the action of mGluR4 on cancer cells. Our study suggested a novel role of mGluR4, which might serve as a potential drug target for control of GBM cell growth.